2021
DOI: 10.1080/26395940.2021.1978868
|View full text |Cite
|
Sign up to set email alerts
|

Alarming carcinogenic and non-carcinogenic risk of heavy metals in Sabalan dam reservoir, Northwest of Iran

Abstract: This research aims to assess contamination status of water and sediment in Sabalan dam reservoir (SDR) and evaluate the impact of water withdrawal depths on the carcinogenic and non-carcinogenic risks of metals for exposed people. Results of metal pollution indices revealed some degree of pollution in water and sediment of the reservoir, especially associated with arsenic. Risk assessment of metals in water of the SDR for non-carcinogenic materials through different scenarios of water withdrawal depth revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Chemical pollution is a further factor to account for as part of water extraction management practices. Aradpour et al [70] reported concentrations of arsenic in the water column and sediment of the Sabalan Dam Reservoir, Iran. A scenario-based risk assessment indicated that water extracted below 10 m can pose a human health risk due to higher concentrations of arsenic at depths exceeding 10 m [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical pollution is a further factor to account for as part of water extraction management practices. Aradpour et al [70] reported concentrations of arsenic in the water column and sediment of the Sabalan Dam Reservoir, Iran. A scenario-based risk assessment indicated that water extracted below 10 m can pose a human health risk due to higher concentrations of arsenic at depths exceeding 10 m [70].…”
Section: Discussionmentioning
confidence: 99%
“…Aradpour et al [70] reported concentrations of arsenic in the water column and sediment of the Sabalan Dam Reservoir, Iran. A scenario-based risk assessment indicated that water extracted below 10 m can pose a human health risk due to higher concentrations of arsenic at depths exceeding 10 m [70]. The results of Aradpour et al [70] and the present findings suggest that water extraction strategies should account for both hazardous chemical and potentially harmful phytoplankton depth profiles in waterbodies known to be polluted.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrochemical concentrations of ions, such as As; K + , Na + , Ca 2+ , Mg 2+ , Cl − , SO 4 2− , HCO 3 − , F − and Br − , the total alkalinity, and total acidity were determined at the Laboratory of the China Geological Survey, Nanjing Center. The arsenic concentration in the groundwater was determined by atomic fluorescence spectrometry.…”
Section: Sampling and Methodsmentioning
confidence: 99%
“…The recommended limit of As concentration in drinking water is 10 µg/L, according to the guidelines for drinking-water quality by the World Health Organization (WHO) [3]. According to the United States Environmental Protection Agency (EPA) and the National Research Council (NRC), the long-term consumption of water with As concentrations as low as 5 µg/L, or even 3 µg/L, might cause adverse chronic health effects on humans, especially cancer [4,5]. Drinking arsenic-rich groundwater is the main route for human exposure to this element.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, health risk assessment (HRA) has become a hot topic with a crucial guiding function in determining whether contaminants pose adverse risks to health and whether groundwater can be drunk directly [28,29]. In recent years, human health risk assessment has been developed and widely used in many countries to determine the adverse effects of chemicals taken from groundwater in different populations [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%